MANAGEMENT OF TAPERING DISORDER IN COCONUT - Kamala Thirumalaiswamy; H. Vijayaraghavan; M.A.J.R. Savery (International Coconut Community Journal, 1994)
The tapering stem wilt of coconut was amply proven to be a physiological disorder, with relevance to physiological and bio chemical investigations of the 14th frond analysis. The experiments, in a rainfed garden, revealed that the occurrence of this malady was mainly due to deficiency of iron, associated with copper and manganese at lower level. The management of this malady was possible by root feeding of micronutrient mixture (Fe+Cu+Mn+B) for two years at six monthly interval. The synergistic effect of Fe, Cu, Mn has indirectly acted on the improvement of tapering disorder, as they are part of metabolic enzymes.